2015
DOI: 10.7752/jpes.2015.01023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The purpose of the research is determination of model of classification of 7-9 th form boy pupils' motor fitness. The methods of the research: for solution of our tasks we used the following methods as analysis of scientific literature, pedagogic testing and methods of mathematical statistic for processing of the obtained results. Discriminant analysis was used as method of simulation. For assessment of functional and motor fitness of 7-9 th form boy pupils we registered results of tests of Shtange, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 7 publications
5
20
0
1
Order By: Relevance
“…Our results also supplemented past research findings concenring methodologic approaches to summarizing control of functional and motor fitness of adolescents (Ivashchenko et al, 2015a(Ivashchenko et al, , 2015b(Ivashchenko et al, , 2015cKhudolii et al, 2015a;.…”
Section: Jpes ®supporting
confidence: 87%
“…Our results also supplemented past research findings concenring methodologic approaches to summarizing control of functional and motor fitness of adolescents (Ivashchenko et al, 2015a(Ivashchenko et al, , 2015b(Ivashchenko et al, , 2015cKhudolii et al, 2015a;.…”
Section: Jpes ®supporting
confidence: 87%
“…These results prove the idea that discriminant model [22,23,28] can be used for pedagogic control of fitness level of 16-17 years' age girls.…”
Section: Results Of the Researchsupporting
confidence: 71%
“…In previous works it was found that discriminant analysis can be effectively used in classification of boys and girls of secondary [23,24,28] and senior forms [21,22]. The received data point at prognostic significance of discriminant function in assessment of schoolchildren's motor and functional fitness [7].…”
mentioning
confidence: 99%
“…The obtained results supplement the data about characteristics of children's and adolescents' motor skills' development (Khudolii, Titarenko, 2010;Khudolii, Ivashchenko, Pimenov, 2012), about possibility to receive new information with the help of simulation method (Iermakov, 2010;Iermakov, Adashevskiy, 2011;Khudolii et al, 2013Khudolii et al, , 2014Supilo, 2014;Muntian, 2013;Ivashchenko, Khudolii, Yermakova, Pilewska, Muszkieta, Stankiewicz, 2015).…”
Section: Discussionsupporting
confidence: 68%